2018
DOI: 10.1002/gsj.1331
|View full text |Cite
|
Sign up to set email alerts
|

Reducing uncertainty in follow‐up foreign direct investment: Imitation by family firms

Abstract: Research Summary This paper examines to what extent family firms rely on imitation when deciding on foreign investment growth, highlighting the role of mimetic isomorphism and social categories. We propose that family firms pursue trait‐based imitation to reduce uncertainty in follow‐up foreign direct investment (FDI), and test our predictions on a large sample of German family firms. We find that family firms imitate successful peers that are also owned by a family. A family firm's tendency to imitate is stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 115 publications
1
12
0
1
Order By: Relevance
“…Still, these studies deal with family multinationals' entry modes, but these firms also have to make entrepreneurial decisions after entering a foreign market in terms of how to manage their investments abroad or even exit and divest. Nevertheless, while scant attention has thus far been paid to entrepreneurial aspects after entry, the few exceptions include the studies by Fourné and Zschoche (2020), Kim et al. (2019) and Zaefarian et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, these studies deal with family multinationals' entry modes, but these firms also have to make entrepreneurial decisions after entering a foreign market in terms of how to manage their investments abroad or even exit and divest. Nevertheless, while scant attention has thus far been paid to entrepreneurial aspects after entry, the few exceptions include the studies by Fourné and Zschoche (2020), Kim et al. (2019) and Zaefarian et al.…”
Section: Resultsmentioning
confidence: 99%
“…'s (2019) perspectives shedding further light on the nuances of international collaborations among family firms. In adopting the problemistic search lens, Fourné and Zschoche (2020) investigate family firms' follow-up FDIs. Interestingly, they provide a complimentary view to the Uppsala model (Johanson and Vahlne, 1977) theorizing that firms reduce uncertainty not only through experiential learning, thereby gradually increasing the commitment to internationalization by acquiring knowledge from their overseas experience, but also through imitation and vicarious learning.…”
Section: Resultsmentioning
confidence: 99%
“…In doing so, we draw on the strategy literature pointing out that the market leader—as the exemplar of a large and successful firm—represents a relevant reference target in information‐based imitation (e.g., Baum et al, 2000; Giachetti & Lanzolla, 2016; Haveman, 1993). Recent studies in the global strategy literature have also shown the relevance of the market leader in internationalization decisions, particularly in location choices (e.g., Fourné & Zschoche, 2020).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Relativamente às fontes de capital próprio internas que financiam os hospitais no seu momento de aquisição, assumem um importante quantitativo (61,7% no Brasil; 100% no Canadá) face aos investimentos realizados. Este resultado está em conformidade com os resultados de outros estudos (Silva, 1994;Lund e Wright, 1999;Fourné, & Zschoche, 2020) que demonstraram que o capital próprio é a principal fonte de capital.…”
Section: Análises De Desempenho Como Apoio a Tomadas De Decisãounclassified